Polimorfismos de genes pró e anti-inflamatórios candidatos à predisposição à rotura prematura de membranas pré-termo e ao trabalho de parto pré-termo - Ramos, Bruna Ribeiro de Andrade [UNESP] (2015)
Introduction: A genetic predisposition to Preterm Labor (PTL) and Preterm Premature Rupture of Membranes (PPROM) has been suggested; however the relevance of polymorphisms and ancestry to susceptibility to PTL and PPROM in different populations remains unclear. Objective: To evaluate the association between Ancestry Informative Markers (AIM) and Single Nucleotide Polymorphisms (SNPs) in Interleukin-1 beta (IL1B), IL6, IL6 Receptor (IL6R), Tumor Necrosis Factor Alpha (TNFA), TNF Receptor (TNFR), IL10, Toll Like Receptor 2 (TLR2), TLR4, Metalloproteinase 9 (MMP9), Tissue Inhibitors of Metalloproteinase 1 (TIMP1) and TIMP2 genes and the susceptibility to PTL and PPROM in Brazilian women. Patients and Methods: Oral swabs were collected from women with PTL and/or PPROM and their babies (PTL: 137 women and 88 babies; PPROM: 64 women and 44 babies) seen at the Botucatu Medical School's Hospital, between 2003 and 2014. Control group included 402 mother-babies pairs of term deliveries, matched to case group by age and newborn gender. After DNA extraction, AIMs were identified by fragment analysis and SNPs by Taqman® SNP Genotyping Assays (Applied Biosystems) and Polymerase Chain Reaction (PCR). The software Structure v2.3.4 was used to estimate ethnic admixture of mothers. Linkage Disequilibrium and Hardy-Weinberg proportions were tested with Genepop 3.4 and haplotypes inferred using Phase. Mann-Whitney, χ2, Fisher's exact test, Logistic Regression models, Odds Ratio and Manova were used in data analysis. Results: Regarding maternal samples, PTL was associated to European ancestry and smoking and African ancestry was protective. Regarding ancestry analysis, self-reported ethnicity only explained 20% and 15% of the global variation in African and European contributions, respectively. Fetal IL10-592 C and IL10-819 C were also associated to PTL. Maternal alleles IL10-1082 G and TLR2 A increased the risk ...